Development of safe and reliable operations in large-scale CO₂ shipping: an experimental approach. - Al Baroudi, Hisham (Cranfield University, 2021)
A successful worldwide implementation of Carbon Capture, Utilisation and Storage largely relies on the establishment of a safe and reliable CO₂ transmission network. CO₂ shipping hereby represents a promising transport option, characterised by a high degree of flexibility in sink-source matching. This study addressed some key knowledge gaps that currently pose a limitation on large-scale commercialisation of this technology by providing information on operational and maintenance challenges in the chain. Firstly, an extensive review of technological advancements and future projections in large scale CO₂ shipping drew the attention to the fact that key technical challenges still need to be addressed in both pipeline and sea vessel systems in order to establish a worldwide network of CO₂ transport infrastructure. In particular, significant dearth concerns the adoption of appropriate safety protocols during accidental scenarios and selection of suitable materials to ensure integrity of transport infrastructure throughout real operations. Thus, an experimental lab scale rig was built and commissioned, capable of handling refrigerated carbon dioxide batches (up to 2.25 L) at conditions typical of sea vessel transport (~0.7 - 2.7 MPa, 223 - 259 K); the facility was designed to permit investigation of accidental leakage behaviour and to determine the qualification assessment of elastomer materials exposed under real shipping conditions. A technical qualification of elastomer materials for CO₂ transport systems was then performed with the aim of assessing their suitability in the intended systems and propensity for degradation. Such elastomers are used as seals in pressure- relief valves, providing elastomer-to-metal shutoff and eliminating leakage around stem during relief mode. Samples previously tested under pipeline conditions (9.5 MPa, 318 K) at exposure times of 50 – 400 h were characterised for a visual inspection, mechanical and thermo-analytical properties. Based on the suitable performance of the elastomers under such pipeline conditions, Ethylene Propylene Diene Monomer was selected for testing under operations typical of CO₂ shipping; constrained (25% compression) samples thereby underwent 20 – 100 CO₂ loading and offloading cycles at average decompression rates of 1.6 MPa/min; tested materials were then qualified through the aforementioned characterisation methodology, demonstrating a satisfactory resistance to rapid gas decompression and mechanical stability. A detailed experimental campaign was considered to assess the accidental leakage behaviour of CO₂ under shipping conditions; the main risks associated with CO₂ are asphyxiation due to displacement of oxygen to critically low levels, and exposure to concentrations of 15% or above in air are deemed life threating due to toxicological impacts on humans. The study highlighted that selection of initial fluid conditions significantly affects the propensity for solid formation in the vessel and blockages in the pipe section, thus resulting in significantly diverse leakage behaviours. Low-pressure decompression tests (0.7 – 0.94 MPa) resulted in the highest amount of inventory solidification (36 – 39 wt%) while high- pressure decompression scenarios (1.8 – 2.65 MPa) demonstrated the lowest (17 – 22 wt%). Lastly, a real-scale investigation on liquid CO₂ discharge from the coupler of an emergency release system was undertaken in order to scrutinise the applicability of such spillage containment measure to CO₂ shipping operations. The study focused on two refrigerated states, namely low- (0.87 – 0.94 MPa, 227 – 231 K) and medium-pressure conditions (1.62 – 1.65 MPa, 239 – 240 K) typical of shipping transport; findings demonstrated the presence of an abrupt outflow behaviour, characterised by full inventory discharge form the coupler in less than 1 s and achievement of peak depressurisation rates of 6 MPa/s. Moreover, the discharge behaviour showed considerable variations in relation to the selected initial conditions.
Keywords: CO₂ transport; CO₂ shipping; leakage behaviour; emergency release system; material selection; refrigerated fluid